La ginocrítica en el ensayo "yunques y crisoles americanos" de Lupe Rumazo. - Quisintuña Tisalema, Jonathan Patricio. (2025)
The research presented below aims to analyze the characteristic elements of Gynocriticism found in Lupe Rumazo's essay "Yunques y crisoles americanos." A qualitative methodology was employed, as it allows for the collection and analysis of non-numerical data to understand concepts, opinions, and experiences. Hermeneutics was also utilized to interpret the texts gathered in the essay, particularly those with a Gynocritical significance. This aided in unraveling symbolic meanings, metaphors, and hidden messages related to the theme. The investigative work was meticulous in gathering the necessary information for analysis. Thus, it was established that Gynocritical elements do exist within the essay, and each of them was analyzed for substantiation. Therefore, it is concluded that the essay "Yunques y crisoles americanos" is rich in female intellectual content. The essay collects experiences and accounts of women who struggled to have their voices heard and their works read. Keywords: Gynocriticism, woman, literature, feminine, struggle.